Chemical Composition, Antimicrobial, Antioxidant, and Antiproliferative Properties of Grapefruit Essential Oil Prepared by Molecular Distillation - Deng, Weihui; Liu, Ke; Cao, Shan; Sun, Jingyu; Zhong, Balian; Chun, Jiong (Molecules (Basel, Switzerland), 2020)
Grapefruit essential oil has been proven to have wide range of bioactivities. However, bioactivity of its molecular distillate has not been well studied. In this study, a light phase oil was obtained by molecular distillation from cold-pressed grapefruit essential oil and GC-MS was used to identify its chemical composition. The antimicrobial activity of the light phase oil was tested by filter paper diffusion method, and the anticancer activity was determined by the Cell Counting Kit-8 (CCK-8) assay. Twenty-four components were detected with a total relative content of 99.74%, including 97.48% of terpenes and 1.66% of oxygenated terpenes. The light phase oil had the best antimicrobial effect on Bacillus subtilis, followed by Escherichia coli, Staphylococcus aureus and Salmonellaty phimurium. DPPH and ABTS assays demonstrated that the light phase oil had good antioxidant activity. The CCK-8 assay of cell proliferation showed that the light phase oil had a good inhibitory effect on the proliferation of HepG2 liver cancer cells and HCT116 colon cancer cells.